2023
DOI: 10.16995/labphon.9112
|View full text |Cite
|
Sign up to set email alerts
|

Bringing indexical orders to non-arbitrary meaning: The case of pitch and politeness in English and Korean

Abstract: In this study, we investigated whether the relationship between pitch and politeness is mediated through iconic relationships between pitch and other talker attributes, and whether these relationships can differ across languages. US and South Korean listeners completed a speaker perception task in which they heard utterances and rated the speaker on a number of attributes, including politeness. The pitch of each utterance was unmanipulated, raised, or lowered. The results confirm previous work suggesting that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…This result was interesting because an increase in pitch has been reported in other languages for polite speech [ 14 ]. Holliday et al [ 15 ] showed that speakers with higher-pitched voices were perceived as being smaller in size, weaker, and more emotional by both Korean and English speakers, supporting [ 16 ], but they were perceived as being less and more polite by Korean and English speakers, respectively. These findings suggest that physical size and emotion are related differently to politeness in the two languages, thereby causing the cross-linguistic differences.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result was interesting because an increase in pitch has been reported in other languages for polite speech [ 14 ]. Holliday et al [ 15 ] showed that speakers with higher-pitched voices were perceived as being smaller in size, weaker, and more emotional by both Korean and English speakers, supporting [ 16 ], but they were perceived as being less and more polite by Korean and English speakers, respectively. These findings suggest that physical size and emotion are related differently to politeness in the two languages, thereby causing the cross-linguistic differences.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that physical size and emotion are related differently to politeness in the two languages, thereby causing the cross-linguistic differences. The same study also found that higher- and lower-pitched speech was perceived as being more friendly and more confident, respectively, in English, whereas Korean showed no such relationship [ 15 ]. These previous studies suggest that the judgment of attributes or personality traits based on acoustic and phonetic cues is complex and culturally bounded.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation